Landas Kontinen Ekstensi dalam Hukum Internasional dan Praktik di Indonesia - Wulandari, Early (Uti Possidetis: Journal of International Law, 2023)
The sea is rich in irreplaceable mineral resources, which are expected to satisfy the world's needs if land resources are insufficient or completely exhausted. This encourages coastal states, including Indonesia, to explore and exploit marine areas, including the continental shelf, which becomes their jurisdiction. One way to increase the area where a country can explore and use its mineral resources is to expand the continental shelf. The purpose of this article is to describe the development and regulation of the extended continental shelf, including its demands, its sovereign rights, and the role of the Commission on the Limits of the Continental Shelf. The article then discusses Indonesia's practice of extending its continental shelf. Therefore, the question arises as to what the international and national agreements are on the extension of the continental shelf and the practice of extending the continental shelf in Indonesia